Functional humanization of immunoglobulin heavy constant gamma 1 Fc domain human FCGRT transgenic mice - Benjamin E. Low; Gregory J. Christianson; Emily Lowell; Wenning Qin; Michael V. Wiles (Taylor & Francis Group, 2020)
A major asset of many monoclonal antibody (mAb)-based biologics is their persistence in circulation. The MHC class I family Fc receptor, FCGRT, is primarily responsible for this extended pharmacokinetic behavior. Engagement of FCGRT with the crystallizable fragment (Fc) domain protects IgG from catabolic elimination, thereby extending the persistence and bioavailability of IgG and related Fc-based biologics. There is a need for reliable in vivo models to facilitate the preclinical development of novel IgG-based biologics. FcRn-humanized mice have been widely accepted as translationally relevant surrogates for IgG-based biologics evaluations. Although such FCGRT-humanized mice, especially the mouse strain, B6.Cg-Fcgrttm1Dcr Tg(FCGRT)32Dcr (abbreviated Tg32), have been substantially validated for modeling humanized IgG-based biologics, there is a recognized caveat - they lack an endogenous source of human IgG that typifies the human competitive condition. Here, we used CRISPR/Cas9-mediated homology-directed repair to equip the hFCGRT Tg32 strain with a human IGHG1 Fc domain. This replacement now results in mice that produce human IgG1 Fc-mouse IgG Fab2 chimeric antibodies at physiologically relevant levels, which can be further heightened by immunization. This endogenous chimeric IgG1 significantly dampens the serum half-life of administered humanized mAbs in an hFCGRT-dependent manner. Thus, such IgG1-Fc humanized mice may provide a more physiologically relevant competitive hFCGRT-humanized mouse model for the preclinical development of human IgG-based biologics.